The Influence of Constructivist Classroom Environment on High School Students’ Mathematics Grades: The Mediating Role of Learning Motivation - Sun, Heyang (International Journal of Social Sciences and Public Administration, 2024)
Constructivist classroom environment scale, mathematics learning motivation scale and mathematics grades were used to investigate 319 students from a high school in a city of Jilin province. The results show that: (1) There is a significant positive correlation between the four dimensions of constructivist classroom environment, such as personal relativity, collaboration, teacher’s support and task orientation, and the constructivist classroom environment can significantly predict mathematics grades. (2) Learning motivation plays an intermediary role between constructivist classroom environment and mathematics grades, and the intermediary role of each path is different.